PERBANDINGAN ESTIMASI SUMBERDAYA BATUBARA MENGGUNAKAN METODE ORDINARY KRIGING DAN METODE CROSS SECTION DI PT. NAN RIANG JAMBI - Reza Taufiqurrahman; Dedi Yulhendra; Adree Octova (Journals Mining Engineering : Bina Tambang, 2015)
PT Nan Riang is one of mining factory which located in Muara Tembesi Subdisctrict, Batanghari Regency, Jambi Province. At this time, PT Nan Riang is exploring coals in which located in Ampelu Village approximately is about 100 hectares, 43 drilling sites. Meanwhile, resource estimation of coals have never been proceed in this area, even though resource estimation is one of important things to do before mining processing. Therefore, we can find out the number of tonnages and sediment models by using resource estimation.  Resource estimation is using two methods there are ordinary kriging method and cross section method. Ordinary kriging method used if the thickness is unknown, and then to estimate the thickness number from an unknown block vertically or horizontally.  So that it will obtain a precipitate in the form of block models in three-dimensional models. After that process, we calculate the volume to get estimation result from coal source. Meanwhile by using cross section method it will count the volume from each slice which has been made in same direction due to coal seam direction. After we got the results from these both methods and then we are comparing and analyzing in order to get the best result, so we can use that result for main reference in carrying out mining activities.  The estimation result by using kriging method will configure model from sediment and the total tonnage of coal. The total tonnage in the research area was 3.237.000 million tonnes, with overburden 15.060.000 bcm. From these calculations we got stripping ratio 4,56 bcm/tonne. We got the estimation result by using cross section method 2.661.647 tons coal tonnage, with overburden 14.459.679 bcm. From the calculation also we got stripping ratio 5,43 bcm/tonne. Because there is a difference from these calculations so we use calculation which has the smallest stripping ratio for using to calculate the production plan